A Copper Coordination Polymer Based on 3-(4-Hydroxypyridinium-1-yl) Phthalic Acid: Synthesis and Crystal Structure. Issue 2 (1st February 2016) - Li, Fu-An; Tian, Qiao-Feng; Yang, Wei-Chun; Bai, Su-Zhen
Abstract : A three-dimensional copper-organic coordination polymer based on 3-(4-hydroxypyridinium-1-yl) phthalic acid (H2 L) and μ-4, 4′-bipyridine (bpy), [Cu(L)(bpy)1/2 (H2 O)] n (1 ), has been obtained by hydrothermal synthesis and characterized by elemental analysis, the powder X-ray diffraction (PXRD), UV–vis absorption spectra, and also by single-crystal X-ray diffraction. The crystal is triclinic, space group P ī. The L 2– anions of complex1 as a bridging ligand connect Cu(II) ions to form one-dimensional (Cu2 (L)2 )n chains, which are linked to build a 2D layer by the bpy ligands. The 3D supramolecular framework of complex1 are guided or controlled by weak directional interlayer hydrogen bond interactions.